Shakespeare & Hathaway : private investigators. Season five [videorecording (DVD)] - Thompson, Paul Matthew; Tindall, Jude (BBC, 2026)
The unlikely crime-fighting duo are back working the cobbled streets of Shakespeare's birthplace to solve more thrilling mysteries and murder most fouls. Grump ex-cop Frank and warm-hearted ex-hairdresser Lu have gone their separate ways. But it's not long before events throw them back together, alongside their Livvie assistant Sebastian. A horror movie director hires the gang when he finds himself terrorized by one of his own creations. A client is fatally electrocuted at a team-building retreat. And a killer is on the loose in an isolate mansion during a murder mystery school reunion. Meanwhile, a saboteur hides in the shadows determined to destroy the Agency. Can Tech Whizz Spider help find the culprit before it's too late?